Cienciometria e análise da variabilidade g enética de variedades de Han cornia speciosa - Nogueira, Cássia Aparecida (2015)
Hancornia speciosa , popularly known as “mangabeira”, is a native fruit tree of the Brazilian Cerrado that has great economic potential due to its multiple uses. The main commercial interest of this species is the fruit production . The fruit can be eaten or processed for the manufacture of jams, jellies, ice cream, juices and liquors among other delicacies. Th is species has a high risk of extinct ion As the use of the species is base d mainly on extractive activity. H. speciosa presents six botanical varieties that they are : speciosa, maximillian i, lundii, cuyab ensis, gardneri e pubescens which morphologically mainly differ by leaf and flower. Despite the species economic potentials, there are few studies on the morphological variation, genetic and pharmacological diversity of mangabeira . Scientometric studies a bout H. speciosa can be useful for conservation and breeding projects of this species, since they can identify deficiencies and helping to direct futures researches As a result, there was a low level of studies of the species, being found only 138 article s published in the last 68 years  In relation to the areas covered by the study, it was noted that there are few studies on the morphological, molecular and pharmacological of different botanical varieties of the species, and these points should be more wi dely used in future research This research identify that there are few studies about morphological, molecular and pharmacological characterization of H. speciosa botanical varieties In relation to genetic variability analysis, two tools were used, molecu lar markers and cytogenetics. The data with molecular markers were generated from the use of microsatellite markers ( EST SSR ) and random markers (RAPD). The results obtained with SSR markers showed a high rate of transferability between C. roseus H. specio sa (75%), low heterozygosity He ) and variability locus (2 or 3 alleles per locus). These results suggest low genetic diversity mangabeira samples. Regarding the spatial distribution, the dissimilarity index of Jaccard and geographical distances, showed no spatial structure of genetic variability. In rela tion to the taxonomy, the us ed markers are not able to distinguish any botanical varieties H. speciosa . The information generated can be used in establishing conservation strategies, as well as in the direc tion of crosses in improvement programs, expanding the knowledge of a species that has economic potential associated with the production of fruit and herbal medicines.